Cells and signals of the leukemic microenvironment that support progression of T-cell acute lymphoblastic leukemia (T-ALL) - Aram Lyu; Seo Hee Nam; Ryan S. Humphrey; Terzah M. Horton; Lauren I. R. Ehrlich (Experimental and Molecular Medicine)
Abstract Current intensified chemotherapy regimens have significantly increased survival rates for pediatric patients with T-cell acute lymphoblastic leukemia (T-ALL), but these treatments can result in serious adverse effects; furthermore, patients who are resistant to chemotherapy or who relapse have inferior outcomes, together highlighting the need for improved therapeutic strategies. Despite recent advances in stratifying T-ALL into molecular subtypes with distinct driver mutations, efforts to target the tumor-intrinsic genomic alterations critical for T-ALL progression have yet to translate into more effective and less toxic therapies. Ample evidence now indicates that extrinsic factors in the leukemic microenvironment are critical for T-ALL growth, infiltration, and therapeutic resistance. Considering the diversity of organs infiltrated by T-ALL cells and the unique cellular components of the microenvironment encountered at each site, it is likely that there are both shared features of tumor-supportive niches across multiple organs and site-specific features that are key to leukemia cell survival. Therefore, elucidating the distinct microenvironmental cues supporting T-ALL in different anatomic locations could reveal novel therapeutic targets to improve therapies. This review summarizes the current understanding of the intricate interplay between leukemia cells and the diverse cells they encounter within their tumor microenvironments (TMEs), as well as opportunities to therapeutically target the leukemic microenvironment.